Palaruan an autism-friendly therapeutic recreation facility - Narida, Ellora Trisha G. (College of Architecture, University of the Philippines Diliman, 2019)
Roughly 1,000,000 Filipinos are diagnosed with autism according the World Health Organization (2017). Autism is primarily associated with difficulties in social interaction and sensory processing but the severity varies with each person, not only making treatment a challenge, but their daily living with family and in their community as well especially with the lack of laws sensitive to their needs. Palaruan is an experimental facility complex designed to be comprehensive early intervention therapy aid for families living with autism through the principles of autism-friendly design and program of responsive play based Dunn's model of sensory processing (2007). Located at the periphery of Santa Rosa, Laguna, Palaruan aims to provide a comforting but engaging experience of therapy to families through play facilities and programs developed in close collaboration with medical specialists. Its first phase consists of three buildings focused on different services: a children's recreation facility with specialized playrooms for mixed public interaction, a training building with learning resources for parents and a therapy center for regular intensive sessions.